National representative seroprevalence of viral hepatitis B, C, and D seromarkers in Ukraine, 2021 - Olena Nesterova (Eurosurveillance, 2025)
BACKGROUND Aligned with World Health Organization (WHO) goals, Ukraine aims to eliminate viral hepatitis. While some data on viral hepatitis B and C prevalence exist among key populations, nationwide prevalence in the general population has never been assessed. AIM To assess the prevalence of viral hepatitis B, C, and D seromarkers in Ukraine in 2021 to plan and monitor elimination measures. METHODS Blood samples available from a cross-sectional household-based SARS-CoV-2 serosurvey conducted in 2021 were tested for hepatitis C virus (HCV) antibodies, total antibodies against hepatitis B virus (HBV) core antigen (HBc), hepatitis B surface antigen (HBsAg) and hepatitis D virus (HDV) antibodies. We calculated crude and weighted proportions for anti-HCV, anti-HBc and HBsAg positivity. To account for differences in sex, age group and urbanisation level, we applied post-stratification weights using inverse probability weighting based on the distribution of the Ukrainian population. We calculated proportions positive for anti-HDV among HBsAg-positive cases and weighted regional estimates for HBV and HCV seromarkers. RESULTS Weighted prevalence of anti-HCV was 3.3% (95% CI: 2.8–4.0), anti-HBc 11.6% (95% CI: 10.8–12.5) and HBsAg 0.9% (95% CI: 0.7–1.2). Among HBsAg-positive individuals, 7.5% (95% СI: 3.0–17.9) were anti-HDV positive. We found higher prevalence of HBV and HCV seromarkers among men and in southern Ukraine. CONCLUSION HBsAg prevalence and considerably high anti-HBc and anti-HCV prevalence indicate substantial lifetime exposure. This reinforces the necessity of sustained prevention such as HBV vaccination of newborns and groups at increased risk, regular hepatitis B and C screening, early treatment, and raising awareness to reduce ongoing transmission.